Pemanfaatan Jahe (Zingiber officinale Rosc) untuk Memacu Pertumbuhan Ikan Nila (Oreochromis niloticus) - Belseran, Lukas; Manoppo, Henky (Universitas Sam Ratulangi, 2015)
A research had been conducted to study the effect ginger supplemented in feed on growth of nile tilapia. Juveniles as much as 250 individuals (mean weight 27.31 g) were obtained from Fish Culture and Development Board (BP3I) Tateli. The fish were placed in plastic bags and transported to Faculty of Fisheries and Marine Science. Fish were then introduced in 15 aquaria at a density of 15 individuals per aquarium. Each aquarium was equipped with an aerator and used water recirculation system. After adaption for one weeks, fish was fed pellet supplemented with ginger powder as treatments at five different doses including A=0, B=2,5, C=5, D=7,5, and E=10 g/kg, each with three replications. Fish was fed treatment diets for four weeks at 3%/bw/day, twice daily at 08.00 am and 17.00 pm. Growth data including absolute and relative growth were weighted at the end of feeding period. Research results showed that after four weeks of feeding, supplementation of ginger powder into fish pellet significantly improved fish growth . The growth of fish fed pellet supplemented with 7.5 g/kg of food was and significantly different as compared to that of control fish. It was concluded that supplementation of ginger powder into fish pellet potentially improved fish growth. Keywords: Ginger, absolute growth, relative growth, nile tilapia